background image

13.5. ADDITIONAL PREDICATES

235

Question

1251

.

Under which conditions it’s true that join of (

α

-,

β

-) totally

bounded reloids is also totally bounded?

13.5. Additional predicates

We may consider also the following predicates expressing different kinds of what

is intuitively is understood as boundness. Their usefulness is unclear, but I present

them for completeness.

totBound

α

(

f

)

totBound

β

(

f

)

• ∃

n

N

E

up

f

: thick

α

(

E

n

)

• ∃

n

N

E

up

f

: thick

β

(

E

n

)

• ∃

n

N

E

up

f

: thick

α

(

E

0

t

. . .

t

E

n

)

• ∃

n

N

E

up

f

: thick

β

(

E

0

t

. . .

t

E

n

)

• ∃

n

N

: totBound

α

(

f

n

)

• ∃

n

N

: totBound

β

(

f

n

)

• ∃

n

N

: totBound

α

(

f

0

t

. . .

t

f

n

)

• ∃

n

N

: totBound

β

(

f

0

t

. . .

t

f

n

)

totBound

α

(

S

(

f

))

totBound

β

(

S

(

f

))

Some of the above defined predicates are equivalent:

Proposition

1252

.

• ∃

n

N

E

up

f

: thick

α

(

E

n

)

⇔ ∃

n

N

: totBound

α

(

f

n

).

• ∃

n

N

E

up

f

: thick

β

(

E

n

)

⇔ ∃

n

N

: totBound

β

(

f

n

).

Proof.

Because for every

E

up

f

some

F

up

f

n

is a subset of

E

n

, we have

E

up

f

: thick

α

(

E

n

)

⇔ ∀

F

up

f

n

: thick

α

(

F

)

and likewise for thick

β

.

Proposition

1253

.

• ∃

n

N

E

up

f

: thick

α

(

E

0

t

. . .

t

E

n

)

⇔ ∃

n

N

: totBound

α

(

f

0

t

. . .

t

f

n

)

• ∃

n

N

E

up

f

: thick

β

(

E

0

t

. . .

t

E

n

)

⇔ ∃

n

N

: totBound

β

(

f

0

t

. . .

t

f

n

)

Proof.

It’s enough to prove

E

up

f

F

up(

f

0

t · · · t

f

n

) :

F

v

E

0

t

. . .

t

E

n

and

(15)

F

up(

f

0

t · · · t

f

n

)

E

up

f

:

E

0

t

. . .

t

E

n

v

F.

(16)

For the formula (

15

take

F

=

E

0

t · · · t

E

n

.

Let’s prove (

16

). Let

F

up(

f

0

t · · · t

f

n

). Using the fact that

F

up

f

i

take

E

i

up

f

for

i

= 0

, . . . , n

such that

E

i

i

v

F

(exercise

1004

and properties of

generalized filter bases) and then

E

=

E

0

u· · ·u

E

n

up

f

. We have

E

0

t

. . .

t

E

n

v

F

.

Proposition

1254

.

All predicates in the above list are pairwise equivalent in

the case if

f

is a uniform space.

Proof.

Because

f

f

=

f

and thus

f

n

=

f

0

t · · · t

f

n

=

S

(

f

) =

f

.